A content analysis of scald first aid information on Chinese websites. Issue 3 (May 2022) - Zhang, Huayu; Yin, Siyuan; Liu, Jian; Li, Xia; Cao, Guoqi; Cao, Yongqian; Ma, Jiaxu; Song, Ru; Zhang, Guang; Wang, Yibing
Highlights: The scald websites established by government agencies and non-profit organizations are few in China. Most of Chinese scald websites are established by commercial companies. Compared with the government agency website, commercial websites contain many advertisements, and their quality and content accuracy need to be further improved. Abstract: Objective: With the rapid development of networks in China, the Internet has become an important source of first aid information for scalds. As a country with the largest population, there are a large number of scald cases every year in China. The content analysis of websites aimed to assess the accuracy and quality of the information on scalds available on Chinese websites. Methods: Using keywords related to scald in the most popular Chinese search engines, 19 sites were eventually selected for evaluation based on the inclusion and exclusion criteria. These websites were assessed on quality and content accuracy by using HONcode, DISCERN, and Patient Education Materials Assessment Tool (PEMAT) evaluation scales, and a modified evaluation system based on the system developed by J.D. Burgess. The evaluation was completed by a 5-person evaluation team. The subjective items were reviewed by five independent reviewers. The objective items were recorded by one reviewer, then another checked the results. Results: Using "scald first aid, " "scald treatment, " and "scald blister" to search on Baidu, Sougou, and Haosou, a total of 180 websites were recorded. According to the inclusion and exclusion criteria, 19 websites were obtained for assessment. Among them, 17 websites (89%) were established by commercial companies. Of the remaining two websites, one was created by a government agency and the other was created by a non-profit organization. The mean total HONcode score, DISCERN score, PEMAT (understandability) score, PEMAT (actionability) score, content accuracy score, and website quality score were 5.19 ± 1.09 out of 8; 52.63 ± 3.69 out of 80; 68%; 56%; 5.05 ± 1.47 out of 8; and 6.11 out of 12, respectively. The scores of the government agency website are better than that of commercial websites. Conclusion: The websites established by government agencies and non-profit organizations are few, and most of the websites are established by commercial companies. Compared with the government agency website, these commercial websites contain many advertisements, and their website quality and accuracy need to be further improved.